Aftershock protect yourself and profit in the next global financial meltdown - Wiedemer, David (John David) (John Wiley & Sons, 2011)
"Aftershock warns of a very different economic future from what most people think. The full impact of the recent bubble pop will create far more problems than we have now, especially for the dollar, and will push home prices and stocks even lower. Unlike most books that try to explain our economic troubles, Aftershock goes beyond the outdated notion of "market cycles" to help readers clearly recognize and quickly respond to the rapidly evolving economy. Things are not going back to how they were before. Instead, we are moving through uncharted territory, with new challenges and opportunities few people anticipate. Aftershock shows readers how to seek safety and profits in these evolving economic conditions. Specifically, the book will: Show readers how to protect assets, businesses, and jobs before and during the coming second wave of the financial meltdown Provide clear and accurate advice on how to profit from the collapsing bubbles Offer focused guidance regarding real estate, which will continue to be a pressing concern for many readers "--